A tale of colorectal carcinoma metastases in the head and neck region: a case report - Ambreen Abdullah Unar,; Fatima Mughis,; Soubia Akhtar,; Maria Syed,; Kanwal Fatima,; Shabbir Akhtar, (Journal of the Pakistan Medical Association, 2024)
Colorectal cancer ideally spreads via the haematogenous or lymphatic route with the most common metastasis to the liver or lungs. Metastasis of this cancer to the parotid gland has not been previously reported. This paper presents a case of rectal adenocarcinoma in a 34-year-old Pakistani male, who presented with histopathological evidence of metastasis in the parotid gland within one year of treatment. He had previously undergone neo-adjuvant chemo-radiotherapy with surgical resection of rectal adenocarcinoma. Metastasis to the parotid gland is an uncommon occurrence in our setting and to our knowledge, this is the first instance of its kind. Careful surveillance of colorectal cancer patients after primary treatment may result in the early recognition of metastases, possibly providing patients with better treatment options and prognosis. This case undoubtedly provides a valuable contribution to the existing literature on colorectal cancer metastasis and points towards the need for additional assessment of these patients post-treatment. Keywords: Colorectal cancer, Metastasis, Parotid gland, Neo-adjuvant.